Interneuron synaptopathy in developing rat cortex induced by the pro-inflammatory cytokine LIF - Engelhardt, Maren; Jamann, Nora (Experimental neurology, 2018)
Pro-inflammatory cytokines of the IL-6 family have been linked to the etiology of epilepsy and mental disorders. After infusion of the IL-6 family member leukemia inhibitory factor (LIF) into postnatal day 12-20 rat visual cortex (period of synaptogenesis; equals early childhood in human) and equivalent ages in organotypic cultures (OTC), somatic growth of cortical and subcortical neurons is delayed, expression of interneuron markers reduced and expression of neurotrophins transiently reduced. Further, LIF prevents NT4 from promoting soma growth of GABA-ergic interneurons. We now show that LIF-treatment from DIV 12-20 in OTC compromises the differentiation of fast-spiking GABA-ergic basket neurons: GAD-65/67, Kv3.2, and synaptotagmin-2 proteins are reduced, dendrites are shorter, and axonal varicosities are smaller. Bitufted and Martinotti interneurons are barely affected. Pyramidal cells display lower dendritic spine densities, more filopodia, and shorter axon initial segments. βIV-spectrin, Cav3.1, GABAA receptor subunits α1 and α2, and the phosphorylation of GluN2B at Y1472 are reduced. The frequency of calcium events in pyramidal cells and interneurons is increased, and the antiepileptic neuropeptide Y is upregulated, suggesting a hyperexcitability of the network. In the presence of LIF, neurotrophins fail to activate MAP kinase phosphorylation and c-fos expression, and exogenous NT4 fails to promote the maturation of pyramidal cells and interneurons as it normally would. After discontinuing LIF treatment, bouton size and expression levels of affected proteins normalize except for synaptotagmin-2; moreover, hyperexcitability persists. The results suggest that elevated levels of inflammatory cytokines during this developmental period cause a lasting maldevelopment in particular of basket cells.
Gesehen am 11.02.2020